2021
DOI: 10.1166/jbmb.2021.2083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drought and Salt Stress on Activities of Antioxidant Protective Enzymes and Expression of Stress Genes in Alfalfa (Medicago sativa L.) Seedlings

Abstract: Drought and salt are main environmental factors that affect the growth, development, productivity and distribution of plants of plants. Alfalfa has a strong ability of early and salt resistance. In this work, the varieties Xinjiang Daye was used as material, the effects of drought (simulated with PEG, polyethylene glycol-6000) and salt stress (with NaCl solution) on the antioxidant capacity of alfalfa seedlings and stress resistance genes was studied, to select alfalfa varieties with strong resistance and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Alfalfa is widely cultivated worldwide and has massive economic advantages on animal husbandry. However, soil salinization has been one of the main factor limiting alfalfa growth (Chen et al, 2021; Lu et al, 2021; Wang et al, 2020). Several studies have been conducted to attempt to identify methods to alleviate the effect caused by salt stress in alfalfa.…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa is widely cultivated worldwide and has massive economic advantages on animal husbandry. However, soil salinization has been one of the main factor limiting alfalfa growth (Chen et al, 2021; Lu et al, 2021; Wang et al, 2020). Several studies have been conducted to attempt to identify methods to alleviate the effect caused by salt stress in alfalfa.…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa possesses four root types (i.e., taproot, branched root, rhizomatous root, and root-tiller type), where rhizomatous alfalfa is more resistant to severe cold due to a grape root neck and a root neck that penetrates deep into the soil (Nan et al 2014). Low temperature induces the production of peroxide isoenzymes, and alfalfa enhances cold resistance by increasing the superoxide dismutase and catalase activities in the root neck, where the superoxide dismutase activity and hypoxidase can be used as physiological indicators of alfalfa ' s cold resistance strength (Chen et al 2021). Through transcriptome sequencing, which mainly focuses on the processes of stress response, hormone regulation and antioxidant regulation, a further analysis revealed that the transcription factor family genes, such as AP2/ERF, WRKY, and MYB, play important regulatory roles in the cold stress process of alfalfa (Zhao et al 2023).…”
mentioning
confidence: 99%